The Riedel Procedure - An Analysis of 22 Cases - William Lawson; Anthony Reino; Robert Deeb (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2017)
Objectives: To report one institution's experience with 22 cases of the Riedel procedure in order to establish a profi le for those patients with chronic frontal sinusitis who develop chronic osteomyelitis. Study Design: Retrospective review.  Methods: Review of all patients undergoing the Riedel procedure at one institution with analysis of demographic data, indications for procedure, technical aspects of performing the procedure, outcomes and complications. Comprehensive review of the literature was performed as well.  Results: Twenty-two patients were identified. The age range in patients varied from 20 years to 86 years. The etiology of the condition requiring the Riedel procedure was infectious in 16 patients, traumatic in 5 and neoplastic in 1. All patients with chronic osteomyelitis of the frontal sinus had undergone multiple intranasal and external procedures. Post-operative follow-up interval ranged from 4 months to 21years.  Conclusion: The Riedel procedure remains a relevant tool in the armamentarium of the rhinologic surgeon. Its primary indication, chronic frontal osteomyelitis, is an indolent process that generally occurs as sequelae of Pott's Puffy tumor, trauma or neoplasm. The natural history is that of multiple failed endoscopic and open procedures. Despite the radical nature of the Riedel procedure, it may not be curative and patients require long term follow up.